Korelasi kadar laktat dengan Score for Neonatal Acute Physiology Perinatal Extension II (SNAPPE II) pada neonatus yang dirawat di NICU RSUP Sanglah, Bali, Indonesia - I Gede Deden Susma Sugara; I Wayan Dharma Artana; Ketut Suarta; Soetjiningsih Soetjiningsih; Ni Putu Siadi Purniti; Dyah Kanya Wati; Made Sukmawati; Made Kardana (DiscoverSys Inc., 2019)
Background: Infant mortality rate is one of the indicators of public health degree that determines the human development index. Various attempts were made to early detect the problems, one of which was by assessing the severity of neonatal disease using Score for Neonatal Acute Physiology Perinatal Extension-II (SNAPPE II) which was associated with lactate levels as a metabolic response and organ dysfunction due to critical illness that were suffered at the Neonatal Intensive Care Unit (NICU).Methods: A cross-sectional analytic study was conducted among 48 critically ill neonates treated at the Sanglah Hospital Denpasar NICU. Samples were selected from affordable populations by consecutive sampling. Data analysis was performed by Saphiro-Wilk data normality test, correlation analysis using the Pearson correlation coefficient, significant results if the value of p <0.05. Data were analyzed using SPSS version 17 for Windows.Results: Most of the respondents were males (67%), the mean of neonatal gestational age was 33 (Â± 3,2) weeks with the median neonatal age at lactate sampling being 24 (24-48) hours. The average age of the mother at delivery was 24 (21-40) years. The mean lactate level in critically ill neonatal patients admitted to the NICU was 3.2 (Â± 0,5) mmol / L. The mean SNAPPE II score on the subject was 32 (20-42). There was a significant positive correlation between the levels of lactate and the severity of the disease in critically ill neonates in the NICU assessed by SNAPPE II (r = 0.45; p = 0.004).Conclusion: Lactate levels has a moderate positive correlation with the severity of the disease in critically ill neonates in the NICU assessed by SNAPPE II